1978
DOI: 10.1128/aac.14.1.95
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Studies with Ambruticin in Murine Histoplasmosis

Abstract: Ambruticin (W7783) was evaluated in vivo in mice subacutely or nonlethally infected with Histoplasma capsulatum. Results were compared with those obtained with amphotericin B, the drug of choice in human histoplasmosis. In one experiment, ambruticin was shown to be capable of curing infected animals as evidenced by totally negative liver and spleen cultures obtained when mice were sacrificed after 4 weeks of oral treatment with 150 mg of drug per kg per day. The 50% cure dose for ambruticin was between 75 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…Similar results have been obtained in mice experimentally infected with H. capsulatum (11). Infections caused by the dermatophytic fungi are among the most common diseases of humans.…”
Section: Discussionsupporting
confidence: 77%
“…Similar results have been obtained in mice experimentally infected with H. capsulatum (11). Infections caused by the dermatophytic fungi are among the most common diseases of humans.…”
Section: Discussionsupporting
confidence: 77%
“…Williams et al (22) found Amph B to prolong survival in nu/nu mice infected with this fungus. Shadomy et al (20) demostrated both life prolongation and biological cures with Amph B in murine histoplasmosis. In the latter study, at doses of 6.25 mg Amph B/kg/day, all spleen cultures were negative for fungi at the end of the 28 day treatment period.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Several studies using ambruticins and their derivatives, in both in vitro and in vivo plant and murine models of fungal infection, have shown therapeutic properties including low toxicity and promising activity against fungal infections including histoplasmosis and coccidiomycosis both intravenously and orally administered. [2,9,10,[12][13][14] Structurally, the ambruticins consist of a trisubstituted divinylcyclopropane ring core appended with two pyrans (Figure 1). Ambruticin congeners vary in the C5 position, but it is the atypical trisubstituted cyclopropane core and promising biological activity that have made these molecules popular synthetic targets.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of the effect of ambruticin VS3 on soil myxobacteria confirms an impact on a group III hybrid histidine kinase (HHK) and provides an environmental advantage by affecting the development of competitive myxobacterial species [11] . Several studies using ambruticins and their derivatives, in both in vitro and in vivo plant and murine models of fungal infection, have shown therapeutic properties including low toxicity and promising activity against fungal infections including histoplasmosis and coccidiomycosis both intravenously and orally administered [2,9,10,12–14] . Structurally, the ambruticins consist of a trisubstituted divinylcyclopropane ring core appended with two pyrans (Figure 1).…”
Section: Introductionmentioning
confidence: 99%